THE EFFECT OF FINANCIAL LITERACY ON BUSINESS E CAPABILITIES AND FINANCIAL ACCESS ON TRADITIONAL MARKET TRADERS - Ai Nety Sumidartini; Suryanto; Nenden kostini; Herwan Abdul Muhyi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The purpose of this study is to determine the influence of financial literacy on business E capabilities and financial access on traditional market traders. This research uses a quantitative approach by using the SEM-PLS application to process and analyze research data. The population in the study included 14,384 small businesses in 25 traditional markets. N = 14,384. Based on the 5% confidence level, it is known as d = 0.05. The results showed that the sample (N) = 389.17 or rounded to 389. The results of the study showed that Financial Literacy has a positive and significant effect on E-Business Capabilities and Financial Literacy has a positive and significant effect on Financial Access.